Pengaruh Fasilitas Pelayanan, Kemampuan Petugas Pelayanan Dan Prosedur Pelayanan Terhadap Kepuasan Kerja Pegawai Rsud Dr.H.Mohamad Rabain - Indra, Meidian; Hardiyansyah, Hardiyansyah; Yusnawati, Yusnawati (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
This study aimed to determine and analyze the influence of service facilities, service officer capabilities, and service procedures, individually and collectively, on the job satisfaction of Dr. H. Mohamad Rabain Regional Hospital employees. The research method used in this study is quantitative, using a questionnaire distributed to respondents. Data quality testing is done using validity tests, reliability tests, and normality tests. The analysis used is descriptive and inferential analysis using statistical calculations with multiple regression formulas, partial tests, simultaneous tests, and coefficient of determination. The study showed that service facilities, service officer capabilities, and service procedures had a significant effect, individually and collectively, on the job satisfaction of Dr. H. Mohamad Rabain Regional Hospital employees